Investigating the relationship between environmental performance and financial performance in the UK industries with the new data of the year 2009 - Wang, Ran (2010)
With the industrial activity development regardless of the negative impact on the natural environment, a certain number of regulations are introduced to address the environmental issues. Sometimes it is not easy for the firms to balance the environmental performance and the financial performance for they tend to maximize the profit in the expense of damaging the environment. Therefore, it is very essential for the firms to take the relationship between these two issues into consideration in order to gain more competitive advantage for the long-term running.